CONCEPTS OF CHILDHOOD EDUCATION TEACHERS REGARDING THE EVALUATION PROCESS - Trevisani, Josiane de Almeida [UNESP]; Souza Filho, Moacir Pereira de (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This paper presents as its theme the evaluation process. Assuming that there is a dichotomy between theory and practice, this paper aims to investigate the practices of teachers of kindergartens and primary schools of Presidente Prudente city. Its purpose is to investigate whether the mediator assessment has not been used due to the completion of paperwork requirements. The research instrument has been based on a questionnaire and the research method was based on Contents Analysis. The results showed that most of the teachers accompanying the students' development, mainly through portfolios. They know the curriculum guidelines, although they do not know of the theoretical framework of the education area. They are supportive of early literacy and pointed to lack the guidance of other professionals.
Keywords: Early Childhood Education; Evaluation; Teachers of Children's Education